Medical Therapy of Acromegaly in Germany 2019 – Data from the German Acromegaly Registry - Quinkler, Marcus; Petroff, David; Knappe, Ulrich J.; Schopohl, Jochen; Tönjes, Anke; Schmid, Sebastian M. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Context Acromegaly is a rare disease caused by excessive growth hormone (GH) secretion from pituitary adenomas in most cases. If neurosurgical therapy is contraindicated or not sufficient, medical therapy is the second line therapy.Objective To describe current medical therapy in acromegaly.Design & Methods Retrospective data analysis from 2732 patients treated in 69 centers of the German Acromegaly Registry. 749 patients were seen within the recent 18 months, of which 420 were on medical therapy (56.1%).Results 73% of medically treated acromegalic patients had normal/low IGF-1 levels. 57% of patients with non-normalized IGF-1 levels had an IGF-1 value between 1- and 1.25-fold above the upper limit of normal. Most patients (55%) received somatostatin analogs as monotherapy, 12% GH receptor monotherapy, and 9% dopamine agonist therapy. Doses of each medical therapy varied widely, with 120 mg lanreotide LAR every 4 weeks, 30 mg octreotide LAR every 4 weeks, 140 mg pegvisomant per week and 1mg cabergoline per week being the most frequent used regimens. A combination of different medical regimens was used in almost 25% of the patients.Conclusion The majority of German acromegalic patients receiving medical therapy are controlled according to normal IGF-1 levels.
Keywords: Acromegaly; growth hormone; IGF-1; cabergoline; lanreotide; octreotide; pegvisomant